Pricing Practices of Nepalese Manufacturing Firms - Nabaraj Adhikari; Eva RA Sitanggang (ABM: International Journal of Administration, Business and Management, 2025)
This research examined the pricing practices of manufacturing firms within the Bankey district of Nepal, focusing on both the objectives and methods employed. Utilizing a Likert-scale questionnaire administered to 67 companies, the study revealed that pricing objectives were predominantly qualitative, prioritizing customer-centric considerations over quantitative targets. The primary pricing methods observed were cost-plus pricing and market-average pricing. Statistical analysis demonstrated a significant relationship between the stated pricing objectives and the methods selected. The study's practical contribution underscores the importance of an integrated pricing framework, wherein managers align their pricing methods with their strategic objectives to enhance performance.